Heterogeneous Catalysts From Rice Husk Modified With Chromium, Molybdenum And Tungsten: Synthesis, Characterization And Application In Styrene Oxidation - Mohamed Iqbal, Mohammad Anwar (2011)
A series of chromium, molybdenum and tungsten incorporated silica extracted from rice husk were prepared at pH 10, pH 7 and pH 3 media using solvent extraction method and sol-gel technique. Liquid phase oxidation of styrene using hydrogen peroxide as oxidant was used as a probe to test their catalytic potential. The incorporation of chromium into the silica matrix resulted in amorphous catalysts labeled RHCr-10, RHCr-7 and RHCr-3. RHCr-3 has the highest surface area (564 m2 g-1) but lowest chromium loading (2.3 w/w %). RHCr-3 showed better structural and catalytic properties compared to RHCr-7 and RHCr-10. About 99.9 % of styrene was successfully oxidized with 63.1 % selectivity towards benzaldehyde.